Archival Romances - Marks, Laura U. (My University, 2017)
Images have a life cycle that is material, social, and imaginative. Their trajectories are especially evident in the work of Arab media artists. Like others in places where official image archives are difficult to access, value glitch, error, and loss of resolution not only for their own aesthetic interest but also as indications of the labor of love required to access the past. Analog demagnetization and lossy digital compression; glitch, error, and artifacts introduced by compression; and layers of formatting draw attention to the trajectories and life cycles of images. Rania Stephan, Mohammad Allam, Riad Yassin, Roy Dib, and other Arab media artists painstakingly amass VHS collections of popular movies and TV shows, in archives that augment in care while they diminish in quality. Other artists including Akram Zaatari, Sophia Al-Maria, and Joana Hadjithomas and Khalil Joreige draw attention to the new meanings that attach to anonymous images as they travel online, finally to be embraced by the recipient.
Found, Compressed and Loved Again
Keywords: 776 Computerkunst (Digitale Kunst)